ChemInform Abstract: One‐Pot Synthesis of 3‐Aryl‐Substituted 1‐Hydroxy‐2‐acylindolizines. Issue 13 (18th March 2013) - Kloubert, Tobias; Kretschmer, Robert; Goerls, Helmar; Krieck, Sven; Westerhausen, Matthias
Abstract Title compounds prepared by reaction of 1, 3‐dicarbonyl compounds (I) with aldehydes are obtained as single crystals and their X‐ray structures are given and discussed.